Low doses of caffeine: Enhancement of physical performance in elite adolescent male soccer players - Ellis, M.; Noon, M.; Myers, T.; Clarke, N. (International Journal of Sports Physiology and Performance, 2019)
Context: High doses of ~6 mg/kg body mass have improved performance during intermittent running, jumping, and agility protocols. However, there are sparse data on low doses of caffeine, especially in elite adolescent soccer players. Methods: A total of 15 elite youth soccer players (177.3 [4.8] cm, 66.9 [7.9] kg, and 16 [1] y) participated in the study, consuming 1, 2, or 3 mg/kg caffeine in a gelatin capsule or a 2-mg/kg placebo in a single-blind, randomized, crossover study design. Testing consisted of a 20-m sprint, arrowhead agility (change of direction [CoD] right or left), countermovement jump (CMJ), and Yo-Yo Intermittent Recovery Test Level 1 (Yo-Yo IR1). Postexercise CMJ performance was assessed as participants exited the Yo-Yo IR1. Data were analyzed using a Bayesian multilevel regression model to provide explained variance and probabilities of improvement (P = %). Results: Compared with placebo, 3 mg/kg caffeine presented the highest probabilities of change across a range of tests (mean [SD], P = %). Times for 20-m sprint were 3.15 (0.10) s vs 3.18 (0.09) s (P = 73%), CoD-right times were 8.43 (0.24) s vs 8.55 (0.25) s (P = 99%), CoD-left times were 8.44 (0.22) s vs 8.52 (0.18) s (P = 85%), Yo-Yo IR1 distance was 2440 (531) m vs 2308 (540) m (P = 15%), and preexercise CMJ height was 41.6 (7.2) cm vs 38 (8.5) cm (P = 96%). Postexercise CMJ was higher with 3 mg·kg-1 than with placebo (42.3 [8] cm vs 36.6 [8] cm; P = 100%). Doses of 1 or 2 mg/kg caffeine also demonstrated the ability to enhance performance but were task dependent. Conclusion: Low doses of caffeine improve performance but are dose and task dependent. A dose of 3 mg/kg caffeine improved performance across the majority of tests with potential to further improve postexercise CMJ height.